Effect of moderate electric field (MEF) treatments on antioxidant capacity and total phenolic compounds of peppermint (menthapiperita) extract. - Kyaw, Thura; Nguyen, Loc Thai; Athapol Noomhorm; Anal, Anil Kumar (Pathum Thani, Thailand : Asian Institute of Technology, 2015)
Moderate electric field (MEF) processing has emerged from the recogniti on that it has significant effect on food and other biological materials. The effect of moderate electric field on antioxidant capacity of DPPH radical scavenging assay and total phenolic content (TPC) assay of peppermint extract was investigated under dif ferent parameters. DPPH and TPC of treated samples were evaluated by chemical analysis as well as electrochemical measurements. A t the given field strength (30 , 40 and 50V/cm), electric fields did no t show any non - thermal degrading effects on antioxidant c apacity while lower DPPH inhibition was detected in the conventionally - treated samples . Field strength 50 V possesses the highest retention capacity of % DPPH inhibition. MEF had no negative effects on DPPH inhibition and TPC contents of plant extracts at different temperatures ( 50, 60 and 70 °C). Low acidic pH of peppermint extract treated by MEF caused significance degradation of DPPH scavenging activity . The results of degradation kinetics reveal sensitive active substances were possibly destroyed during preheating and only stable active components can survive over long studied time. According to cyclic volt ammetry results , reduction in the peak current between the initial and final treatments of both MEF and conventional heating indicated that antioxidan t capacity of the polyphenols decreased gradually.
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Engineering in Food Engineering and Bioprocess Technology, School of Environment, Resources and Development
Thesis (M. Sc.) - Asian Institute of Technology, 2015
Keywords: Bioactive compounds; Electrochemical analysis; Antioxidants; Extraction (Chemistry)